Effects of a Single Intravitreal Injection of Aflibercept and Ranibizumab on Glomeruli of Monkeys - Tschulakow, Alexander (PLoS One, 2014)
PURPOSE: It is known that endothelial cells in the kidney are also strongly VEGF-dependent. Whether intravitreal drugs can be detected within the glomeruli or affect VEGF in glomerular podocytes is not known. Therefore, the aim of this pilot study was to investigate the effects of a single intravitreal injection of aflibercept and ranibizumab on glomeruli of monkeys. METHODS: The kidneys of eight cynomolgus monkeys, which were intravitreally injected either with 2 mg of aflibercept or with 0.5 mg of ranibizumab, were investigated one and seven days after injection. Two animals served as controls. The distribution of aflibercept, ranibizumab and VEGF was evaluated using anti-Fc- or anti-F(ab)-fragment and anti-VEGF antibodies respectively. The ratio of stained area/nuclei was calculated using a semi-quantitative computer assisted method. Glomerular endothelial cell fenestration was quantified in electron microscopy using a systematic uniform random sampling protocol and estimating the ratio of fenestrae per µm. RESULTS: Compared to the controls, the anti-VEGF stained area/nuclei ratio of the ranibizumab-treated animals showed no significant changes whereas the stained areas of the aflibercept-treated monkeys showed a significant decrease post-treatment. Immune reactivity (IR) against aflibercept or ranibizumab was detected in aflibercept- or ranibizumab treated animals respectively. The number of fenestrations of the glomerular endothelial cells has shown no significant differences except one day after aflibercept injection in which the number was increased. CONCLUSION: Surprisingly, both drugs could be detected within the capillaries of the glomeruli. After a single intravitreal injection of aflibercept, VEGF IR in the podocytes was significantly reduced compared to controls. Ranibizumab injection had no significant effect on the glomeruli's VEGF level. Whether this is caused by aflibercept's higher affinity to VEGF or because it is used in a higher stoichiometric concentration compared to ranibizumab remains to be investigated.